The Influence of Storytelling and Learning Concentration on the Narrative Text Listening Ability of Fourth-Grade Students at SD Negeri 1 Kulo - Hasniati; Muhammad Hanafi; Jumiati; Yusmah; Aswadi; Jamaluddin Ahmad (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examines the influence of storytelling and learning concentration on the narrative text listening ability of fourth-grade students at SD Negeri 1 Kulo. Specifically, it analyzes (1) the partial effect of audio storytelling, (2) the partial effect of learning concentration, and (3) the simultaneous effect of both variables on students’ narrative text listening skills. Employing a quantitative ex post facto design with a correlational approach, the study involved the entire population of 34 fourth-grade students as the sample through saturated sampling technique. Data were collected using questionnaires, classroom observation, and a narrative listening test, and analyzed through descriptive statistics, normality testing (Kolmogorov-Smirnov), multiple linear regression, t-test, and F-test. Descriptive results indicated that audio storytelling (M = 35.6), learning concentration (M = 40.2), and narrative listening ability (M = 75.6) all fell into the “good” category. Normality tests confirmed that all variables were normally distributed (p > 0.05). The partial t-test revealed significant positive effects for both audio storytelling (t = 3.52, p = 0.001) and learning concentration (t = 3.38, p = 0.002). The simultaneous F-test further confirmed a significant joint influence (F = 24.381, p = 0.000). The findings demonstrate that audio storytelling and learning concentration exert positive and significant partial and simultaneous effects on fourth-grade students’ narrative text listening ability. These results offer practical implications for elementary language teachers seeking innovative, media-supported strategies to enhance listening comprehension.